Roxadustat regulates the cell cycle and inhibits proliferation of mesangial cells via the hypoxia-inducible factor-1α/P53/P21 pathway - Cheng, Yun; Yang, Qingmei; Feng, Baijie; Yang, Xiuhong; Jin, Huimin (Frontiers in Cell and Developmental Biology, 2025)
BackgroundOver-proliferation of mesangial cells (MCs) is one of the main pathological changes in the early stages of diabetic kidney disease (DKD). Roxadustat, an oral hypoxia-inducible factor (HIF) prolyl hydroxylase inhibitor, is widely studied in different models of kidney disease. Whether roxadustat has beneficial effect on the proliferation of MCs and DKD remains unknown.MethodsThe optimal concentration of roxadustat for inhibiting MC proliferation was determined using CCK-8 and colony formation assays. Changes in the cell cycle were detected using flow cytometry, and changes in cell cycle-related proteins were screened using quantitative reverse transcription polymerase chain reaction. Reverse experiments were applied using Trp53-/- cell line. Co-immunoprecipitation was used to verify the interaction between HIF-1α and p53 and predict sites of interaction. Finally, a corresponding in vivo verification was performed.ResultsOptimal concentrations of high glucose (30 mM) and roxadustat (100 μM) were established. Roxadustat showed anti-proliferation effect on MCs through S-phase arrest. HIF-1α/p53/p21 and downstream cyclins (cyclin A1, cyclin A2, and cyclin E1) showed corresponding changes. A reverse experiment confirmed that HIF-1α affected cell cycle and proliferation through p53, and co-immunoprecipitation results showed a interaction between HIF-1α and p53. Molecular docking predicted the possible interaction between Lys328, Pro332, Arg245, and Lys251 of HIF-1α and Ala222, Tyr226, Glu225, and Asp265 of p53, respectively. Finally, animal experiments demonstrated similar effect of roxadustat in db/db mice.ConclusionRoxadustat regulates and inhibits cell proliferation of MCs via the HIF-1α/p53/p21 pathway. This may be a potential therapeutic target in the early stages of diabetic kidney disease.